Application of scanning electron microscopy–energy dispersive X-Ray spectroscopy (SEM-EDS) - Girão, Ana Violeta (2017)
In scanning electron microscopy (SEM), a highly energetic and focused electron beam scans the sample and normally provides an extremely enlarged image of the morphology of the sample, as well as information on its chemical composition using an energy dispersive spectrometer (EDS) detector. SEM-EDS is mainly used for characterization of materials, but lately its application has been extended to study organic-based specimens, such as biological samples and polymers.Microplastics are hazardous materials produced not only directly by anthropogenic activities but also as a resulting product of macroplastics degradation. Pollution due to release of micro/nanoplastics into the environment and their ecological consequences are nowadays subject of extended scientific research. Consequently, the demand of dedicated techniques for the assessment of morphology and chemical nature of such polymer-based materials is of utmost importance.This chapter highlights the recent application of SEM-EDS for the characterization of microplastics as emergent pollutants. SEM-EDS is an advanced imaging and analytical technique that effortlessly copes with the urgent need for the characterization of such waste products as well as the other toxic substances that may be adsorbed by microplastics. The prominence of electron microscopy coupled with analytical detectors, particularly SEM-EDS, in the identification and determination of morphology of micro/nanoplastics can undoubtedly be established.